1990
DOI: 10.1007/bf00226155
|View full text |Cite
|
Sign up to set email alerts
|

Genome size variation in Zea mays ssp. mays adapted to different altitudes

Abstract: Previous studies have indicated a positive correlation between genome size and altitude among plant species. It has been hypothesized that increasing genome size occurs due to increasing C-banded heterochromatin. In corn, increasing altitude has been correlated with decreasing knob (C-banded) heterochromatin, suggesting that DNA content may decrease with increasing altitude. In this study, nuclear DNA content of 12 southwestern United States Indian maize populations, collected at various altitudes, was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(59 citation statements)
references
References 10 publications
6
51
1
1
Order By: Relevance
“…This variation has been in accordance with (Rayburn and Auger, 1990) who found a significant positive correlation between genome size of corn and altitude, suggesting that corn follows the trend of increasing DNA content with increasing altitude. Kron et al (2007) revealed that the individuals of Eryngium duriaei from higher altitudes presented a significantly higher genome size than those belonging to populations from lower altitudes.…”
Section: Ajabssupporting
confidence: 91%
“…This variation has been in accordance with (Rayburn and Auger, 1990) who found a significant positive correlation between genome size of corn and altitude, suggesting that corn follows the trend of increasing DNA content with increasing altitude. Kron et al (2007) revealed that the individuals of Eryngium duriaei from higher altitudes presented a significantly higher genome size than those belonging to populations from lower altitudes.…”
Section: Ajabssupporting
confidence: 91%
“…Thus, the most likely explanation for these differences is the differential proliferation (and (or) deletion) of transposable elements among populations. This hypothesis has previously been suggested as the mechanism of genome size variation in various plant species (e.g., Rayburn and Auger 1990;Bennetzen et al 2005) but has not been studied in depth within animals or crustaceans specifically. Transposable elements have been characterized from different crustacean lineages (e.g., Casse et al 2006;Vergilino et al 2013), though their direct contributions to differences in genome size have not yet been quantified.…”
Section: Discussionmentioning
confidence: 99%
“…Al respecto cabe recordar que diversos trabajos han mostrado importantes variaciones en el contenido de ADN entre poblaciones cultivadas que proceden de diferentes regiones o climas en maíz (Laurie y Bennett, 1985), arroz (Iyengar y Sen, 1978) y soya (Rayburn y Auger, 1990;Rayburn et al, 1997). Sin embargo, antes de llegar a conclusiones definitivas sobre el papel de la reestructuración cromosómica en la evolución de Tamarindus indica se debe reunir más información detallada sobre la extensión de la variabilidad en el número, morfología y longitudes cromosó-micas en el intervalo de su distribución geográfica en poblaciones del Nuevo Mundo, especialmente de México.…”
Section: Discusión Y Conclusionesunclassified